Effect of artificial gravity on neurocognitive performance during head-down tilt bedrest - Borbála Tölgyesi; Anna Altbäcker; Irén Barkaszi; Tim Stuckenschneider; Leonard Braunsmann; Endre Takács; Bea Ehmann; László Balázs; Vera Abeln (npj Microgravity, 2024)
Abstract This study evaluated the acute and chronic effects of intermittent and continuous Artificial Gravity (AG) on cognitive performance during 60 days of Head-down tilt bedrest (HDTBR), a well-established ground-based spaceflight analogue method. Participants were randomly assigned to three groups: intermittent AG, continuous AG, and HDTBR control group without AG exposure. Task performance and electrophysiological measures of attention and working memory were investigated during Simple and Complex tasks in the Visual and the Auditory modality. Compared to baseline, faster reaction time and better accuracy was present during HDTBR regarding the Complex tasks, however, the practice effect was diminished in the three HDTBR groups compared to an ambulatory control group. Brain potentials showed a modality-specific decrease, as P3a was decreased only in the Auditory, while P3b decreased in the Visual modality. No evidence for acute or chronic AG-related cognitive impairments during HDTBR was found.